The Role of Microloans, Informal Employment, and Income in Reducing Poverty in Eastern Indonesia - Suratini; Jolyne Myrell Parera; Imran Syafei M. Nur; Maria Yuvita Gobay (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study analyzes the influence of microloans, the availability of informal employment, and income levels on poverty rates in the Eastern Indonesia region. Using panel data from 13 provinces over the 2020–2022 period and a Random Effect Model regression method, the results show that microloans and the availability of informal employment significantly contribute to reducing poverty, while income levels do not have a significant partial effect. However, collectively, the three variables have a significant impact on poverty rates. These findings highlight the importance of expanding access to microloans and improving the quality of informal employment to support poverty alleviation efforts. Microloans can help low-income individuals start or grow small businesses, while the informal sector provides job opportunities for those not absorbed into the formal labor market.